How is mobile broadband intensity affecting CO₂ emissions? – A macro analysis - Harald Edquist; Pernilla Bergmark (International Telecommunications Society (ITS), 2022)
This paper investigates the association between relative mobile broadband penetration and carbon dioxide (CO2) emissions globally. The study is based on 181 countries for the period 2002-2020. The results indicate an initial increase in CO2 emissions for a country at an average emission level once mobile broadband is introduced. Possible explanations might be initial investment in network infrastructure and increased consumption of electricity. However, on average for the period 2002-2020 the continuous relationship between mobile broadband (defined as speeds of at least 256 kbps) and CO2 is significantly negative, i.e. emissions at a country level significantly reduce as mobile broadband penetration increase. Based on a two-stage model and controlling for fixed broadband and four addition control variables (i.e. population density, electricity consumption from fossil fuel, industry as a share of GDP and a regulation index), we are able to conclude that on average a 10 percentage points increase in mobile broadband penetration causes a 7 percent reduction of CO2 emissions per capita (given that the instrumental variable strategy, as assumed, identifies causal effects). Thus, the results show that investments in mobile infrastructure over longer periods of time can contribute to mitigating climate change.
Keywords: O13; O33; Q54; 330; Mobile broadband; carbon dioxide (CO2); climate change